2015 IEEE 42nd Photovoltaic Specialist Conference (PVSC) 2015
DOI: 10.1109/pvsc.2015.7356061
|View full text |Cite
|
Sign up to set email alerts
|

Mercury: Industrial IBC cell with front floating emitter for 20.9% and higher efficiency

Abstract: In this paper break-through results on our 6" industrial Mercury cells are presented. We gained more than 1% absolute in efficiency by optimizing the processes and design of the cells, resulting in 20.9% cell efficiency. We used standard industrial equipment and the number of process steps similar to our commercial n-Pasha technology. The screen-printed IBC cells can be interconnected by our proven industrial foil-based interconnection scheme. Together with this result, we present a method to characterize and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…ECN's IBC concept Mercury, based on a FFE, has so far reached conversion efficiencies up to 21.1%. [4], [5] Although the problems of electrical shading thus can be minimized, in this work it will be shown that another mechanism can induce a significant loss in performance for diffused-junction IBC solar cells. Specifically, it will be shown that a distinctive charge-carrier recombination current can be associated with the presence of the pn-junctions which border the at the rear surface of the solar cell.…”
Section: Introductionmentioning
confidence: 95%
“…ECN's IBC concept Mercury, based on a FFE, has so far reached conversion efficiencies up to 21.1%. [4], [5] Although the problems of electrical shading thus can be minimized, in this work it will be shown that another mechanism can induce a significant loss in performance for diffused-junction IBC solar cells. Specifically, it will be shown that a distinctive charge-carrier recombination current can be associated with the presence of the pn-junctions which border the at the rear surface of the solar cell.…”
Section: Introductionmentioning
confidence: 95%